Vitamin D Deficiency Is Not Associated with Diabetic Retinopathy or Maculopathy - Uazman Alam; Yasar Amjad; Anges Wan Shan Chan; Omar Asghar; Ioannis N. Petropoulos; Rayaz A. Malik (Journal of Diabetes Research)
Background. Experimental and clinical studies suggest a possible association between vitamin D deficiency and both diabetic retinopathy and maculopathy. Methods. We have performed a cross-sectional study in adults with types 1 and 2 diabetes mellitus. The relationship between the presence and severity of diabetic retinopathy and maculopathy with serum 25-hydroxyvitamin D concentration was evaluated using logistic regression analyses in the presence of demographic and clinical covariates. Results. 657 adults with diabetes were stratified based on retinopathy grading: No Diabetic Retinopathy (39%), Background Diabetic Retinopathy (37%), Preproliferative Diabetic Retinopathy (21%), and Proliferative Diabetic Retinopathy (3%), respectively. There were no differences in serum 25-hydroxyvitamin D concentrations (25(OH)D) between the groups (15.3±9.0 versus 16.4±10.5 versus 15.9±10.4 versus 15.7±8.5 ng/mL, P=NS). Logistic regression analysis demonstrated no statistically significant relationship between the severity of retinopathy and serum 25(OH)D. Furthermore, there was no difference in serum 25(OH)D between those with (n=94, 14%) and those without (n=563, 86%) Diabetic Maculopathy (16.2±10.0 versus 15.8±9.8, P=NS) and no relationship was demonstrated by logistic regression analyses between the two variables. Conclusions. This study has found no association between serum 25(OH)D and the presence and severity of diabetic retinopathy or maculopathy.